The Carboniferous shoshonitic (s.l.) gabbro-monzonitic stocks of Veiros and Vale de Maceira, Ossa-Morena Zone (SW Iberian Massif): evidence for diverse subduction-related lithospheric metasomatism - Amaral, João Lains (2022)
Post-collisional potassium-rich rocks are a critical petrogenetic and geodynamic marker across the European Variscan Belt. We present a detailed characterization of the only potassium-rich mafic intrusions identified so far in the Ossa-Morena Zone (Iberian Massif). Using new major, trace and Smsingle bondNd isotopic whole-rock analyses, as well as mineral chemistry analyses, we discussed the petrogenesis of the early Carboniferous potassium-rich Veiros and Vale de Maceira (Portugal) stocks in the geotectonic framework of the southern Iberia, marked by the collision of the Ossa-Morena Zone, a Gondwanan terrane, with the South Portuguese Zone, a Laurussian terrane. The Veiros and Vale de Maceira shoshonites (s.l.) range from gabbros to syenites, with a predominance of monzonites and monzogabbros, characterized by different proportions of olivine, clinopyroxene, orthopyroxene, plagioclase, alkali feldspar, phlogopite and brown hornblende. The Veiros stock is mainly composed of fine-grained ultrapotassic rocks, and the Vale de Maceira stock is composed chiefly of medium-grained shoshonite rocks. A small group of hornblende-bearing medium-grained calk-alkaline rocks was also identified. The stocks have high contents of K2O, MgO, total alkalis, Th and other LILE, high ratios of LREE/HREE and LREE /HFSE, and show a Nb-Ta-Ti negative anomaly, typical of orogenic settings. Sr and Nd isotopes yielded moderate radiogenic Sr and unradiogenic Nd, that might suggest the involvement of a crustal component. However, the combined use of isotopic and elemental compositions rules out significant contamination by crustal materials upon ascent and emplacement. Instead, a source metasomatised by subduction-related fluids and hydrous melts from the slab is proposed. This diversely metasomatised source was a phlogopite-amphibole-bearing and (phlogopite-free) amphibole-bearing lherzolite at the upper part of the garnet stability field in the sub-continental lithospheric mantle. The Devonian mafic volcanic rocks point to a northward dipping (present coordinates) subduction of the Rheic oceanic plate underneath the Ossa-Morena Zone during the Variscan Orogeny. However, the Veiros and Vale de Maceira magmas originated during the post-collisional stage from the partial melting of the supra-subduction metasomatized lithosphere. The melting occurred during a period of enhanced heat due to asthenospheric upwelling related to the slab break-off of the Rheic's slab. The stocks are concomitant with the profusion of granitoid intrusions, which is compatible with a post-collisional tectonic setting. They are also coeval with the opening of the Beja-Acebuches back-arc, likely related to slab roll-back of a segment of the Rheic oceanic crust, implying polyphasic subduction and a complex geodynamic setting for the late stages of oceanic closure in southern Iberia.